Kinerja Keuangan Daerah dan Hubungan dengan SilPA di Kabupaten Bungo - H.Izudin H. Izudin; Syaparudin Syaparuddin; Syamsuddin HM Syamsuddin HM (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2013)
Budget Revenues and Expenditures should be managed properly and correctly, noted that financial management shall indicator of the success of the viewable area if the area of financial performance have been implemented effectively and efficiently, the impact of the effectiveness and efficiency of lead remaining in Over Budget Calculation known pleased with SiLPA, for the author want to know the district noted that financial performance is connected dengnan Bunge Silpa with the aim of (1) determine the relationship of SiLPA Revenue Bungo Regency period 2001-2010 (2) to determine the relationship Silpa-forming component with the period 2001-2010 SiLPA Bungo district, (3) to determine effectiveness and efficiency of financial management Bungo district in 2001-2010, and (4) to determine whether the effectiveness and efficiency affects the Silpa. Data analysis methods used in this study is the analysis of secondary data from Government Financial Statements consisting of Bungo District Budget Realization report, Balance Sheet, Statement of Cash Flow from Revenue Management Agency Regional Finance and Asset District Bungp years 2001-2010 and data derived from the Regional Planning Board Bungo District. By using the formula analysis korelaisi and regression Karl Person's and the analysis of the ratio obtained (1) The relationship of income of Regional against SiLPA is in the category of very low, low and medium, (2) The relationship components of  SiLPA with SiLPA is in the category of moderate, strong and very strong, (3) The effectiveness of financial management are in the category of effective and very effective., for efficiency is in the category are not efficient, less efficient and reasonably efficient (4) Effect of the effectiveness of 1.419 means SiLPA event of excess revenue will mempengeruhi SiLPA increased by 1.42 percent and the efficiency of minus 0.389 SiLPA mean if there is a reduction / savings will affect the increase in spending of 0.39 percent SiLPA.   Keywords: SiLPA, Budget, Financial Management